Observations, Evaluations, and Recommendations for DETERLab from an Educational Perspective - Ahmed Ibrahim; Vitaly Ford (Journal of Cybersecurity Education, Research & Practice)
DETERLab is a cluster environment that provides a set of virtual machines that can be used by researchers and teachers to run cybersecurity experiments and competitions, and where it is possible to deploy different network configurations to research attack and defense mechanisms in the cyber world. While we were working to develop a pathway for producing more usable and effective cybersecurity educational resources by investigating and examining several projects, we examined DETERLab as a prospective platform to use in the classroom. Throughout our experimentation, we faced challenges that we decided to document in order to help other educators use the environment effectively. In this article, we reflect on the application process, available resources, getting started, and running experiments. We also include an analysis of experiments that have a step-by-step guide, sample solution, grading criteria, network diagram, and teacher manual. In addition, we reflect on the environment for usage in a classroom setting and list all available materials as of the time of writing this article. We believe that DETERLab has the potential to be widely adopted in cybersecurity courses to develop the necessary skills if the key user experience and technical challenges mentioned in this article are addressed. As part of our future work, the findings in this article will be compared to other projects in a much larger research study aiming to develop a pathway for producing more usable and effective cybersecurity educational resources.